Intergenerational educational trajectories and lower back pain in young women and men - Lourenço, S (2017)
We examined the association between intergenerational educational trajectories and lower back pain (LBP) outcomes in young women and men from the general population. Participants were part of the 21 years old follow-up of the EPITeen cohort study, which was set up during the 2003/2004 school year and recruited subjects born in 1990 attending schools in Porto, Portugal (n=1657, 51.6% women). Parental and individual educational levels were used to define intergenerational edu cational trajectories as stable-high, upward, stablelow, and downward. Data on the presence, severity and chronicity of LBP were also assessed. Gender-specific adjusted odds ratios (OR) with 95% confidence intervals (95% CI) were computed to estimate the associations between educational trajectories and LBP outcomes. When compared to women with stable-high educational trajectories, those with stable-low educational trajectories were significantly more likely to report moderate/severe (adjusted OR=1.76, 95% CI: 1.21-2.57) and chronic (adjusted OR=1.82, 95% CI: 1.02-3.22) LBP. The magnitude of these associations was even stronger among females with downward educational trajectories (moderate/severe: adjusted OR=2.58, 95% CI: 1.49-4.46; chronic: adjusted OR=2.42, 95% CI: 1.12-5.27). Educational trajectories were not significantly associated to LBP outcomes among men. In conclusion, intergenerational educational trajectories may contribute to LBP as reported in early adulthood, particularly in women.